Radio Spectral Energy Distribution of Low-z Metal Poor Extreme Starburst Galaxies: Novel insights on the escape of ionizing photons - Bait, Omkar; Schaerer, Daniel; Izotov, Yuri; Sebastian, Biny (My University, 2025)
Recent optical surveys have identified a rare population of low-z (z ~ 0.01 - 0.06) extreme star-forming galaxies (xSFGs) characterized by very low metallicity, strong emission lines, extremely high specific star-formation rate, low stellar mass, and strong Lyα emission. Their global properties resemble recently discovered z > 6 reionization-era star-forming galaxies. We present new multi-frequency radio continuum (RC) observations of 8 xSFGs using the upgraded Giant Metrewave Radio Telescope (uGMRT) at 1.25 GHz, the Karl G. Jansky Very Large Array (VLA) at 1.5, 3.0, 6.0, 10.0 and 15.0 GHz, along with archival LOw Frequency ARray (LOFAR) data at 150 MHz for several sources. These data allow construction of the radio spectral energy distribution (radio-SED) from ~1 GHz (down to 150 MHz for some sources) to 15 GHz, spanning nearly two orders of magnitude in frequency. We find that xSFGs exhibit a flat spectral index between 6 and 15 GHz, while a subset shows spectral turnovers at 0.3 - 3 GHz. Our Bayesian radio-SED modeling indicates that these features are consistent with a high thermal fraction combined with free-free absorption, requiring high emission measures in some systems. By comparing modeled thermal radio emission with observed Hβ line flux density, we find evidence for dust in several xSFGs. Finally, we confirm a previously reported correlation between Lyman continuum escape fraction, ionization state, and radio spectral index, particularly among strong leakers.
Keywords: galaxies: starburst; galaxies: dwarf; galaxies: ISM; radio continuum: galaxies; radio continuum: ISM; dark ages; reionization; first stars